Removal of T cells from bone marrow for transplantation: a monoclonal antilymphocyte antibody that fixes human complement. - Hale, G; Bright, S; Chumbley, G; Hoang, T; Metcalf, D; Munro, A; Waldmann, H (1983)
Graft-versus-host disease is one of the major problems in clinical bone marrow transplantation. Many experiments in animals have shown that it could be greatly reduced if mature T lymphocytes were removed from the donor marrow. Here we describe a new rat monoclonal antibody, CAMPATH 1, which is suitable for depleting lymphocytes from human marrow grafts. CAMPATH 1 is an IgM that fixes human complement. It binds to both T and B lymphocytes and some monocytes but not to other hemopoietic cells. When peripheral blood mononuclear cells were treated with CAMPATH 1 and complement, more than 99% of lymphocytes were killed and viable T cells could no longer be detected. Under these conditions, in vitro multipotential erythroid and myeloid colony-forming cells were unaffected. As well as being used for in vitro treatment of bone marrow to remove T cells, CAMPATH 1 could potentially be applied to other experimental and clinical situations where depletion of lymphoid cells is required, including serotherapy to achieve immunosuppression for organ transplants or to treat lymphocytic leukemias.